2021
DOI: 10.3390/ani11030725
|View full text |Cite
|
Sign up to set email alerts
|

Researching Human-Cattle Interaction on Rangelands: Challenges and Potential Solutions

Abstract: Human-animal interaction (HAI) research spans across many scientific fields and animal taxa. For livestock species, HAI research tends to focus on animals that are managed in close proximity with humans such as poultry, dairy cattle, and swine. Given the nature of rangeland cattle production, HAI research with beef cattle often occurs in and around the processing environment. This high arousal context may skew behavioral and physiological responses by the animals due to the potentially negative interaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 142 publications
1
7
0
Order By: Relevance
“…Cortisol levels were interestingly shown to significantly interact with breed and week, indicating that the two breeds may handle stress differently over time. Our results are in line with earlier studies (31,32), which have demonstrated that breed can considerably affect the stress response of cattle during handling activities. Furthermore, the observed alterations in the stress response over time emphasize the significance of taking into account the long-term impacts of handling stress on animal welfare and output.…”
Section: Discussionsupporting
confidence: 93%
“…Cortisol levels were interestingly shown to significantly interact with breed and week, indicating that the two breeds may handle stress differently over time. Our results are in line with earlier studies (31,32), which have demonstrated that breed can considerably affect the stress response of cattle during handling activities. Furthermore, the observed alterations in the stress response over time emphasize the significance of taking into account the long-term impacts of handling stress on animal welfare and output.…”
Section: Discussionsupporting
confidence: 93%
“…In 2021, an article was published that focused on positive management: Positive Human Contact and Housing Systems Impact the Responses of Piglets to Various Stressors [34]; The Ethics of Touch and the Importance of Nonhuman Relationships in Animal Agriculture [35]; Researching Human-Cattle Interaction on Rangelands: Challenges and Potential Solutions [36]; Human-animal relationship influences husbandry practices, animal welfare and productivity in pig farming [37]; Costs and Benefits of Improving Farm Animal Welfare [38]; and Human-animal relations in business and society: Advancing the feminist interpretation of stakeholder theory [39]. Also in 2021, three important lectures occurred during the writing of this article: two in Brazil, whose authors were França [40] and Néstor [41] and one in Portugal, by Ceballos [42].…”
Section: State Of the Artmentioning
confidence: 99%
“…Animal–human interaction varies the animal’s behavioral and physiological response resulting, in some cases, in a stressful stimulus for the animal. Depending on the magnitude and type of the stressful stimuli, animals can modulate their physiological response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%